Nombres comerciales en kichwa en Quito: una comodificación y explotación cultural del uso de la lengua - Enríquez Duque, Paola (2022)
The Kichwa language is used in commercial names in Quito, the capital of Ecuador, where most of the population self-identifies as mestizo and does not speak Kichwa. The usage of Kichwa is very limited in social interactions in Quito, yet its presence in the city’s linguistic landscape is evident. These names are associated with concepts like organic, artisanal, or national; and so assign an additional commercial value to the product. Accordingly, surveys and interviews show that the meanings of Kichwa words in commercial names are unknown by the population. This use of the Kichwa language represents a case of cultural exploitation as it is causing the language to be resignified through a process of language commodification resulting in commercial benefits.